Nasal myiasis: Report of a case and literature review (2016)
Myiasis is the infection of animal or human tissues or organs by larvae of Diptera. It may affect individuals of any age, but is more common in middle-aged and elderly patients. Nasal myiasis, an infection of the nasal and paranasal cavities by such larvae, is a common disease in tropical and developing countries. Reported cases of nasal myiasis have been caused by several different species, such as Lucilia sericata in Korea and Iran, Estro ovis in Algeria and France, Lucilia cuprina and Phaenicia sericata in Malaysia, Cochliomyia hominivorax in French Guiana, Drosophila melanogaster in Turkey, Eristalis tenax in Iran and Oestrus ovis in Israel. Signs and symptoms are related to the presence and movement of the larvae, and include foreign body sensation, bloody or muco-purulent nasal discharge. Prevention may be done with insect repellent. Treatment is based on antiparasitic drugs and techniques for removal of larvae, but may include the use of prophylactic topical or systemic antibiotics for possible secondary infections. We report a case of nasal and left maxillary sinus myiasis in an elderly woman, who responded favorably to treatment. © 2016, Universidad de Antioquia. All rights reserved.